The Efficacy And Screening Of Crude And Hydrolyzed Methanolic Extracts Of Tridax Procumbens (L.) Against Aedes Albopictus (Skuse) And Aedes Aegypti (L.). Dinesh A/L Rajendran - Rajendran, Dinesh (2019)
The epidemic of dengue and Zika outbreak transmitted by Aedes mosquitoes has been a global issue and plenty of preventive measurements are being used. Due to environmental awareness, people are opting on bioinsecticides. The objective of this research is to study the effectiveness of crude and hydrolyzed extracts of Tridax procumbens plant on Aedes aegypti and Aedes albopictus larvae and to investigate the larvicidal compound present in T. procumbens. Using WHO larval bioassay, third instar larvae of Ae. aegypti and Ae. albopictus were exposed to different concentration ranging between 250-2500 ppm of six different parts of Tridax plant methanolic extracts (flower, stem, leaves, roots, aerial part containing flower, stem and leaves and whole plant) extracted using Soxhlet extraction. The highest toxicity for Ae. aegypti was recorded by Tridax stem crude extract with the LC50 of 799.78 ppm and LC95 of 1506.66 ppm. Meanwhile for Ae. albopictus, it was recorded by Tridax flower crude extract with the LC50 of 583.63 ppm and LC95 of 2329.41 ppm. The selected extract of T. procumbens which were the stem, flower and leaves were then hydrolyzed by boiling with 2M of HCl and re-extracted with ethyl acetate to remove glycosides from the bioactive compounds in T. procumbens.